2006
DOI: 10.1182/blood-2005-02-0802
|View full text |Cite
|
Sign up to set email alerts
|

Cellular prion protein is released on exosomes from activated platelets

Abstract: Cellular prion protein (PrP C ) is a glycophosphatidylinositol (GPI)-anchored protein, of unknown function, found in a number of tissues throughout the body, including several blood components of which platelets constitute the largest reservoir in humans. It is widely believed that a misfolded, protease-resistant form of PrP C , PrP Sc , is responsible for the transmissible spongiform encephalopathy (TSE) group of fatal neurodegenerative diseases. Although the pathogenesis of TSEs is poorly understood, it is k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
83
1
1

Year Published

2006
2006
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(92 citation statements)
references
References 46 publications
(43 reference statements)
7
83
1
1
Order By: Relevance
“…In fact, recent studies using the dissociation-enhanced lanthanide fluoroimmunoassay showed that platelets and plasma are the main reservoir of cellassociated prion protein in human blood. 76 Similar studies also indicate that this protein is released from platelets obtained by apheresis during storage. 77 Evidence that these infectious prion particles are associated with platelet-derived MP suggests that the latter play a role in their spread.…”
Section: Role Of MV In Hiv and Prion Transfersupporting
confidence: 54%
See 1 more Smart Citation
“…In fact, recent studies using the dissociation-enhanced lanthanide fluoroimmunoassay showed that platelets and plasma are the main reservoir of cellassociated prion protein in human blood. 76 Similar studies also indicate that this protein is released from platelets obtained by apheresis during storage. 77 Evidence that these infectious prion particles are associated with platelet-derived MP suggests that the latter play a role in their spread.…”
Section: Role Of MV In Hiv and Prion Transfersupporting
confidence: 54%
“…Furthermore, as MV membranes engulf some cytoplasm during membrane blebbing, they may also contain proteins derived from it and mRNA. 17,18 Moreover, they may 'hijack' infectious particles (e.g., human immuno deficiency virus (HIV) or prions) from the cytoplasm [19][20][21][22] or possibly even whole intact organelles such as the mitochondria. 23 MV are released by various cell types and differ in composition depending on cell origin and status.…”
Section: Introductionmentioning
confidence: 99%
“…Little is known about the distribution of PrP TSE in blood. PrP C has been detected in exosomes isolated from platelets and annexin V-positive EVs released from apoptotic endothelial cells (48,56). These findings raise the possibility that endothelial and blood cells other than platelets may be capable of releasing PrP C and possibly PrP TSE in association with exosomes and other types of EVs, contributing to the transmission of TSEs through blood-derived products (48, 56 -58).…”
mentioning
confidence: 76%
“…Experimental detection of PrP TSE in animal cerebrospinal fluid (CSF) (29), whole blood (21,22), plasma (27)(28)(29)(30)71), buffy coat (24 -26), and urine (74) and in human CSF (12,75), whole blood (6 -8), and urine (76,77) has been achieved by different methods that rely on the concentration or amplification techniques to bring PrP TSE levels to the detection threshold of biochemical assays. Although the presence of PrP TSE in blood exosomes has been suggested previously (48), biochemical detection has been complicated by the low levels of PrP TSE in blood and the concomitantly large volumes required for exosome isolation by standard methods. Traditionally, exosome isolation has been achieved by a series of differential centrifugation and filtration steps from large sample volumes (68).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation